Political Behavior - steven Greene (Plenum Publishing Corporation, 2002)
Buku ini Berisi Beberapa penelitian dengan judul The social- Psychological Measurement Of Partisanship, Party Polarization And Party Structuring Of Policy Attitudes: A Comparison Of Three Nes Panel Studies, Explaining Women's Rights Realignment: Convention Delegates, 1972-1992, Culture Wars,Secular Realigment. And The Gender Gap In Party Identification